Penerapan Media E-Leaflet Digital sebagai Upaya Peningkatan Literasi Kesehatan Pasien Demam Tifoid di Rumah Sakit - Cahyanto, Heri Nur; Lantasary, Mira Dwi; Mayasari, Nabilla; Prasetyo, Joko; Singgih, Singgih (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Typhoid fever remains a major public health issue in Indonesia, especially in areas with poor sanitation and low health literacy. The disease, caused by Salmonella typhi, can lead to prolonged fever, digestive disorders, and serious complications if not treated properly. Limited understanding of prevention and poor hygiene practices often result in recurrent infections. The growing use of digital technology in healthcare provides new opportunities for patient education through interactive and accessible media such as e-leaflets. Objective: This community service aimed to improve patients’ knowledge and hygienic behavior in preventing typhoid reinfection through the use of e-leaflet media as an innovative digital health education tool. Method: The program was conducted by lecturers and students from the Medical-Surgical Nursing specialization, Master of Nursing Program, Universitas Strada Indonesia. The activity took place from September 15 to October 15, 2025, at Bhayangkara Hospital TK II H.S. Samsoeri Mertojoso Surabaya, involving 40 patients and family members in the Anyelir 1, Edelweis, and Sakura wards. Activities included coordination with hospital staff, design of an interactive e-leaflet integrated with a QR code, education sessions, and discussions. Knowledge was assessed using pre- and post-tests based on the Knowledge, Attitude, and Practice (KAP) framework, and analyzed descriptively. Result: The average knowledge score increased from 60.00 ± 7.85 before to 82.00 ± 6.42 after the intervention (p = 0.000). Participants found the e-leaflet engaging, easy to access, and helpful in understanding typhoid prevention. Conclusion: The e-leaflet is an effective digital health education tool that enhances patient knowledge and hygiene practices to prevent typhoid reinfection.